Desvelando as tramas e os dramas da inclusão escolar: um estudo com professores do ensino fundamental - Cardoso, Cristiane Dos Reis (2017)
School inclusion is a theme that generates a lot of controversy and resistance among the educators, fact that can be visualized taking as base the segregative or integrative actions that do not support the development and the learning of the students at all. Using this understanding and having as a base the Human Development investigation in the Cultural Hiscoric theory's perspective, this work's general goal is to analyze the subjectivation relations of the teachers' performance in the school inclusion process for students with disabilities. In order to reach the proposed goals, the research was developed in a State School from the municipality of Alfenas/MG, in the module schedule of teachers of two turns, having a total of 28 participants. The research is qualitative and is based on the dialectical method, that has as study object the historical subject, and includes research-intervention assumptions. As resources, were used the questionnaire os participant(s) characterization; the phrases, mediating materialities and triggering issues complement. The information was recorded and registered in the field journal and qualitatively assessed adopting the elaboration of a Nucleus of Meaning, entitled: "The Plots and Dramas of School Inclusion", from this Nucleus four indicators could be contemplated: the impact of social inequality in the family/school relation; the inclusion as socialization versus the compensation and the referrals; the naturalization of the representation of teachers' inability versus the continued formation for inclusive performance and inclusion as an isolated teachers' action versus the institutional understanding of the defectology. As final considerations, we could observe the importance of the continued fomation in the space in which the professionals act, in such a way to enable the problematization of the teachers' restlessness facing the inclusive education along with the manager team, and through these moments of trades and outbursts overcome the several different feelings that surround students with disabilities. We understand it is urgent to install dinamics and dialogue processes that enable the subjects to position themselves, disagree, agree, reflect, within their real possibilities of development in the individual and social spheres, about the scenarium in which they act.